Higher-Order Conditioning: What Is Learnt and How it Is Expressed - Honey, Robert C.; Dwyer, Dominic M. (Frontiers in Behavioral Neuroscience, 2021)
Pairing a neutral conditioned stimulus (CS) with a motivationally significant unconditioned stimulus (US) results in the CS coming to elicit conditioned responses (CRs). The widespread significance and translational value of Pavlovian conditioning is increased by the fact that pairing two neutral CSs (A and X) enables conditioning with X to affect behavior to A. There are two traditional informal accounts of such higher-order conditioning, which build on more formal associative analyses of Pavlovian conditioning. But, higher-order conditioning and indeed Pavlovian conditioning have characteristics that are beyond these accounts: Notably, the two are influenced in different ways by the same experimental manipulations, and both generate conditioned responses that do not reflect the US per se. Here, we present a formal analysis that sought to address these characteristics.